Biomonitoring of Aristolactam-DNA Adducts in Human Tissues using Ultra-Performance Liquid Chromatography/Ion-Trap Mass Spectrometry - Yun, Byeong Hwa (2012)
Aristolochic acids (AAs) are a structurally-related family of nephrotoxic and carcinogenic nitrophenanthrene compounds found in Aristolochia herbaceous plants, many of which have been used worldwide for medicinal purposes. AAs have been implicated in the etiology of so-called Chinese herbs nephropathy and of Balkan endemic nephropathy. Both of these disease syndromes are associated with carcinomas of the upper urinary tract (UUC). 8-Methoxy-6-nitrophenanthro-[3,4-d]-1,3-dioxolo-5-carboxylic acid (AA-I) is a principal component of Aristolochia herbs. Following metabolic activation, AA-I reacts with DNA to form aristolactam (AL-I)-DNA adducts. We have developed a sensitive analytical method, using ultra-performance liquid chromatography-electrospray ionization/multistage mass spectrometry (UPLC-ESI/MS(n)) with a linear quadrupole ion-trap mass spectrometer, to measure 7-(deoxyadenosin-N(6)-yl) aristolactam I (dA-AL-I) and 7-(deoxyguanosin-N(2)-yl) aristolactam I (dG-AL-I) adducts. Using 10 μg of DNA for measurements, the lower limits of quantitation of dA-AL-I and dG-AL-I are, respectively, 0.3 and 1.0 adducts per 10(8) DNA bases. We have used UPLC-ESI/MS(n) to quantify AL-DNA adducts in tissues of rodents exposed to AA, and in the renal cortex of patients with UUC who reside in Taiwan, where the incidence of this uncommon cancer is the highest reported for any country in the world. In human tissues, dA-AL-I was detected at levels ranging from 9 to 338 adducts per 10(8) DNA bases, whereas dG-AL-I was not found. We conclude that UPLC-ESI/MS(n) is a highly sensitive, specific and robust analytical method, positioned to supplant (32)P-postlabeling techniques currently used for biomonitoring of DNA adducts in human tissues. Importantly, UPLC-ESI/MS(n) could be used to document exposure to AA, the toxicant responsible for AA nephropathy and its associated UUC.